2013
DOI: 10.1074/jbc.m112.387712
|View full text |Cite
|
Sign up to set email alerts
|

Watching the Bacteriophage N4 RNA Polymerase Transcription by Time-dependent Soak-trigger-freeze X-ray Crystallography

Abstract: Background:The two-metal-ion mechanism of the nucleotidyl transfer reaction by RNA/DNA polymerases has not been adequately elucidated due to lack of temporal resolution. Results: Soak-trigger-freeze x-ray crystallography revealed structures of natural, time-resolved intermediates of transcript initiation. Conclusion: First structural evidence shows that catalytic metal binds after the nucleotide and nucleotide-binding metal and right before reaction chemistry. Significance: Time-dependent soak-trigger-freeze x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…However, the stopped-flow data with non-extendable DNA and Ca 2ϩ resulted in a poor fit to the same three-step model indicating that the non-covalent step is abolished under these conditions. This observation of the non-covalent step (step 3.1), taken together with the non-hydrolyzable analog data and the observation that step 3 (fingers closing) was similar with Ca 2ϩ and Mg 2ϩ , may be a result of a rearrangement of the active site (Asp-256, Asp-190, and Asp-192) during the binding of metal A, as recently suggested (23,34,39,42,55). Other possibilities include local rearrangement of active site side chains as recently suggested (44).…”
Section: Scheme 2 Biochemical Pathway Model For Kintek Explorer Simumentioning
confidence: 78%
“…However, the stopped-flow data with non-extendable DNA and Ca 2ϩ resulted in a poor fit to the same three-step model indicating that the non-covalent step is abolished under these conditions. This observation of the non-covalent step (step 3.1), taken together with the non-hydrolyzable analog data and the observation that step 3 (fingers closing) was similar with Ca 2ϩ and Mg 2ϩ , may be a result of a rearrangement of the active site (Asp-256, Asp-190, and Asp-192) during the binding of metal A, as recently suggested (23,34,39,42,55). Other possibilities include local rearrangement of active site side chains as recently suggested (44).…”
Section: Scheme 2 Biochemical Pathway Model For Kintek Explorer Simumentioning
confidence: 78%
“…Triphosphate intensity reduction showed that catalysis was complete shortly after 10 minutes. Basu and Murakami 40 used the Raman kinetic data to flash freeze and solve the structures of the N4 crystals at time points between the 0 to 10 minutes of soak in. The predictions from Raman crystallography were borne out, they were able to obtain high quality X-ray structures for intermediates during the formation of the covalent nucleic acid backbone bond.…”
Section: Discussionmentioning
confidence: 99%
“…The in crystallo transcription system can be used to study RNA transcription by Raman crystallography and time-resolved trigger-freeze crystallography. Analogous to the studies performed on single-subunit RNAPs (41,42), these new experimental approaches may allow to trace events in not only initial transcription but also during the NTP addition cycle in cellular RNAPs.…”
Section: Discussionmentioning
confidence: 99%